Looking Into the Entanglement Between Karst Landforms and Fault Activity in Carbonate Ridges: The Fibreno Fault System (Central Italy) - Saroli, Michele; Albano, Matteo; Moro, Marco; Falcucci, Emanuela; Gori, Stefano; Galadini, Fabrizio; Petitta, Marco (Frontiers in Earth Science, 2022)
The entanglement between active tectonics and karst systems is well-known in the literature. Karst systems are sound recorders of continental deformation in terms of brittle structures and seismic features and have been successfully used as markers for reconstructing tectonic stresses and assessing preferential directions of increased permeability in oil and gas fields. Karst systems could also be exploited to evaluate the past activity of faults bounding karst hydrostructures, thus providing useful data for the assessment of the seismic hazard of a specific area. In this work, we look into the complex relationship among karst development, recent tectonics and groundwater flow, which appear to be strongly interconnected with each other, to assess the activity of faults bounding karst hydrostructures. We focused our attention on an active karst area located in the Mesozoic and Cenozoic carbonate reliefs of the Italian central Apennines. In this context, the morphological and morphometric features of the karst landforms (dolines, dry valleys, and cave entrances), identified with geomorphological surveys, and their mutual relationship with fractures and fault segments, identified employing geostructural analysis, document stasis and deepening events in karst evolution. Such events are related to changes in the groundwater table and the consequent variation of the paleokarst base level associated with the Quaternary fault activity. A comprehensive evaluation of the evolution of karst systems at local and regional scales, considering the hydrogeological influence on base levels, allows us to use karst landforms as a proxy to unravel fault activity and evolution in Italy other similar karst environments.